The Nature of Humanity in the Quran: Perspective of Islamic Educational Philosophy - Dellawati, Dellawati; Sunarto, Sunarto (International Journal Corner of Educational Research, 2025)
The nature of humans in the concept of Islamic education is a creature created by Allah SWT who can develop all the potential they have as well as possible without neglecting anything at all. The basic potential of human nature must be designed optimally and integrated through a lifelong education process. The research method used in obtaining data in this article is qualitative research with libraries, which takes data from the literature used to search for concepts, theories, opinions, or discoveries that are closely related to the main problem of this research. Based on the explanation in the discussion section, it can be concluded: (1) the terms used in the Qur'an in referring to humans are al-Insan (referring to humans who have special qualities and potential), al-Basyar (referring to humans as biological creatures), and al-Nas (referring to humans as social creatures); (2) The views of the figures on the nature of humans differ but the essence is the same, namely humans as creatures who have different potential from other creatures of Allah; (3) Humans are referred to as ahsan al-taqwin which places humans in a strategic position, namely as servants of Allah and as caliphs of Allah